(untitled) (Research, Society and Development, 2021)
Objective: To identify through the literature the importance of clinical assessment of nurses to establish a care plan for children in the face of peripheral venipuncture and describe the main actions that nurses can promote, pharmacological or not, in order to promote comfort to the child during the process. of venipuncture. Methodology: integrative review, with a search in the Virtual Health Library (VHL), LILACS, BDENF and MEDLINE. Results: Selection of 10 articles that served as the basis for the study. Content analysis and discussion: three categories were created: clinical assessment of nurses in Intravenous Therapy; the child and the peripheral venipuncture procedure; and the actions of nurses in assisting children with AVP. Conclusion: It is essential to rethink the practice and know that it is possible to reduce complications for the patient, improving the knowledge of the entire Nursing team about the catheter, for quality care, in which the nurse plays a crucial role in continuing education, where its continuous update regarding new health technologies is necessary.